Correction: N/O co-enriched graphene hydrogels as high-performance electrodes for aqueous symmetric supercapacitors. Issue 36 (22nd June 2021) - Zhang, Yong; Wei, Liang; Liu, Xijun; Ma, Wenhui; Wang, Jiankai; Fan, Shan
Abstract : Correction for 'N/O co-enriched graphene hydrogels as high-performance electrodes for aqueous symmetric supercapacitors' by Yong Zhang et al., RSC Adv., 2021, 11, 19737–19746, DOI: ; 10.1039/D1RA01863A .